1999
DOI: 10.1152/ajpendo.1999.277.1.e135
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I in skeletal muscle after weight-lifting exercise in frail elders

Abstract: To assess muscle remodeling and functional adaptation to exercise and diet interventions, 26 men and women aged 72–98 yr underwent a vastus lateralis biopsy before and after placebo control condition, and progressive resistance training, multinutrient supplementation, or both. Type II atrophy, Z band, and myofibril damage were present at baseline. Combined weight lifting and nutritional supplementation increased strength by 257 ± 62% ( P = 0.0001) and type II fiber area by 10.1 ± 9.0% ( P = 0.033), with a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 28 publications
13
154
2
4
Order By: Relevance
“…In this study diminished muscle levels of insulin-like growth factor-I (mIGF-I) were identified in our RA patients. This finding is consistent with reports of reduced mIGF-I levels in other conditions characterised by muscle wasting: chronic heart failure (CHF) (Hambrecht et al, 2005), chronic obstructive pulmonary disease (COPD) (Vogiatzis et al, 2007), chronic renal failure (Macdonald et al, 2004(Macdonald et al, , 2005, and advanced aging (Fiatarone Singh et al, 1999); and with the proposed role of mIGF-I in regulating the maintenance of adult skeletal muscle (Adams, 2002). Following 24 weeks PRT, along with muscle hypertrophy, mIGF-I levels were observed to increase 50% in our RA patients.…”
Section: Impact On Mechanisms Of Rheumatoid Cachexiasupporting
confidence: 92%
See 1 more Smart Citation
“…In this study diminished muscle levels of insulin-like growth factor-I (mIGF-I) were identified in our RA patients. This finding is consistent with reports of reduced mIGF-I levels in other conditions characterised by muscle wasting: chronic heart failure (CHF) (Hambrecht et al, 2005), chronic obstructive pulmonary disease (COPD) (Vogiatzis et al, 2007), chronic renal failure (Macdonald et al, 2004(Macdonald et al, , 2005, and advanced aging (Fiatarone Singh et al, 1999); and with the proposed role of mIGF-I in regulating the maintenance of adult skeletal muscle (Adams, 2002). Following 24 weeks PRT, along with muscle hypertrophy, mIGF-I levels were observed to increase 50% in our RA patients.…”
Section: Impact On Mechanisms Of Rheumatoid Cachexiasupporting
confidence: 92%
“…Following 24 weeks PRT, along with muscle hypertrophy, mIGF-I levels were observed to increase 50% in our RA patients. Again, this finding of coincident increases in mIGF-I levels and muscle mass in cachectic individuals following exercise training is consistent with responses in COPD (Vogiatzis et al, 2007) and dialysis (Macdonald et al, 2005) patients, and the frail elderly (Fiatarone Singh et al, 1999); and the pivotal role put forward for mIGF-I in muscle's hypertrophic response to loading (Adams, 2002).…”
Section: Impact On Mechanisms Of Rheumatoid Cachexiasupporting
confidence: 75%
“…Moreover, resistance training may lead to other hormonal changes, such as in circulating levels of growth hormone (GH) and intramuscular insulin-like growth factor-1 (IGF-1), which are well described among healthy older adults. 11,12 In prostate cancer patients, no data are currently available on the acute effects of resistance training on these growth factors and increased circulating levels of GH and IGF-1 in prostate cancer patients may help to improve physical function and quality of life, and to preserve body composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, our positive data were obtained using a mixture of amino acids alone, while the studies demonstrating no benefit [62][63][64] or some benefit [65] from nutritional supplements in older adults utilized a balanced meal consisting of protein, fat, and carbohydrate [62][63][64]. Thus, the differences in the makeup of the nutritional supplements could have been responsible for the disparity between studies.…”
Section: Mixed Nutrient Feeding and Muscle Protein Anabolism In Agingmentioning
confidence: 86%
“…Moreover, the addition of nutritional supplementation to resistance exercise did not increase muscle mass, strength, and/or muscle protein synthesis above the level achieved with resistive exercise alone [62][63][64]. Nonetheless, in a follow up study, it was found that increasing energy intake was associated with positive changes in strength and type II fiber size [65].…”
Section: Mixed Nutrient Feeding and Muscle Protein Anabolism In Agingmentioning
confidence: 90%